Protective effects of resveratrol on hepatic ischemia reperfusion injury in streptozotocin-induced diabetic rats - ELÇİOĞLU, HATİCE KÜBRA; KABASAKAL, LEVENT; TETİK, ŞERMİN; ŞEKERLER, TURGUT (SPRINGER, 2019)
Resveratrol (RSV) is a natural polyphenolic compound having antioxidant effects. This study was designed to investigate the protective effects of resveratrol against oxidative stress in hepatic ischemia-reperfusion (I/R) injury in streptozotocin (STZ)-induced diabetic rats. STZ was injected intraperitonally (i.p.) to 18 Sprague-Dawley albino rats, which were divided into three groups, each having six rats. First group was non-treated diabetic group (D), second diabetic group was subjected to 30 min of hepatic ischemia followed by a 45-min reperfusion period (D + I/R), and third diabetic group was subjected to 30 min of hepatic ischemia followed by a 45-min reperfusion period and treated with 20 mg/kg/day oral RSV before 30 min I/R injury (D + I/R + RSV). At the end of the experimental period, animals were decapitated, and blood samples were collected to determine tissue tumor necrosis factor-alpha (TNF-alpha) levels. Liver and lung tissue samples were obtained for the evaluation of biochemical parameters including malondialdehyde (MDA) and glutathione (GSH) levels and histopathological examinations. Compared to control, I/R injury resulted in decreases in GSH levels and increases in MDA levels. Tissue TNF-alpha levels were also increased in the D + I/R group compared to D group. Treatment with RSV prevented the alterations on biochemical parameters and histopathological changes induced by I/R. We demonstrate that in diabetic rats, hepatic I/R injury is associated with an augmented inflammatory response and oxidative stress, while RSV pre-treatment significantly decreased these responses. Larger clinical studies are desirable to determine the exact role(s) of RSV on hepatic I/R injury among diabetic subjects.
Keywords: Resveratrol; Diabetes; Ischemia reperfusion injury; Inflammation; Experimental rats; ALPHA-LIPOIC ACID; OXIDATIVE STRESS; ISCHEMIA/REPERFUSION INJURY; CEREBRAL-ISCHEMIA; SIGNALING PATHWAY; LIVER; INFLAMMATION; MICE